Duopoly pricing of software products under free strategy: Limited-feature vs. seeding. (October 2016) - Nan, Guofang; Shi, Feihong; Dou, Runliang; Li, Minqiang
Highlights: We consider two free strategies for software products in duopoly environment. We explore how the optimal prices and profits are affected. The limited-feature free trial may be provided with lower quality and better service. It is profitable for the firm adopting seeding strategy to seed more consumers. Seeding strategy suits for higher seeding ratio and stronger network intensity. Abstract: Adopting free strategy in competitive settings is pervasive in the software market. However, previous studies on free trial pay more attention to monopoly case rather than duopoly case. This paper examines the duopoly case in which one firm adopts the limited-feature free trial strategy and the other employs the seeding strategy. We drive the equilibrium prices and profits of two firms, and explore how the optimal prices and profits are affected by the quality and the service level of free trial version, the network intensity and the seeding ratio. We find that the firm adopting the limited-feature free trial strategy is profitable to provide free trial version of its commercial software with lower quality and better service, and the firm which uses seeding strategy may seed more potential consumers to obtain more profit. We discover the impact of the network intensity is negative on the profit of the firm that adopts the limited-feature free strategy. This result is different from the previous literature on limited-feature free trial in monopoly case. Moreover, the firm which employs seeding strategy prefers higher seeding ratio and stronger network intensity.